The Trouble with Islam - Nergis Mazid (International Institute of Islamic Thought, 2004)
Set up as an open letter to Muslims, Irshad Manji’s book contains one letter, nine chapters, six pages of recommended readings, and three pages of acknowledgement. Together the 247 pages charge that “[t]otalitarian impulses lurk in mainstream Islam” (p. 3, original emphasis) and reform is crucial for the world’s security. Her open letter informs readers that “Islam is on very thin ice” (p. 1) with her, and asks for her charges to be heard. She then provides an autobiographical narrative that jumps from her days as a youngster in a Baptist after school program to a madressa and junior high school. It moves to her career as a journalist pioneering QueerTelevision then to 9/11 and its aftermath. Interwoven between these brief accounts are her indictments of Islam and Muslims. She ends the book with her bid for reform. In a colloquial style, Manji lays her heavy charge: mainstream Muslims are “intellectually atrophied and morally impaired” (p. 55). Regardless of their location, they are universally homophobic, anti-Semitic, and misogynistic. Those arguing otherwise are ignorant, fraudulently cry racism or injustice when criticized, and are compliant in all the gross human rights violations occurring in Muslim countries. Muslims who promote Islam’s egalitarian message and reconcile contradictions by engaging in discourse and contextualizing the Qur’an, the Shari`ah, and the Hadith, or cite cultural influence to renounce stoning, rape laws, or discrimination are not, according to her, following mainstream Islam as they would like to think. Rather, they are acting despite it. Islam, according to Manji, is “really” a tribal religion that is centrally controlled by Arabs who interpret the “Koran,” a contradictory book suffering from “a mountain range of moods” (p. 228), to propagate “desert Islam.” Globally, Muslims cling to “foundamentalism,” a glorification of the Islam of the past, which actually was not as egalitarian as they claim. This, along with Arab imperialism, are responsible for the social ills of Muslims, not western imperialism, colonialism, or “the Jewish conspiracy.” Nonetheless, with Orientalist tropes and her western-cultivated commitment to fairness and the individual, which, she informs, did not evolve from Islam, Manji says there is room for Islam – as long as it reforms. “Operation Ijtihad” involves questioning Islam, its tenets, and proponents by reviving ...